Analysis of neurodevelopmental outcomes of preadolescents born with extremely low weight revealed impairments in multiple developmental domains despite absence of cognitive impairment - Viena Tommiska; Aulikki Lano; Päivi Kleemola; Liisa Klenberg; Liisa Lehtonen; Tuija Löppönen; Päivi Olsen; Outi Tammela; Vineta Fellman; Finnish ELBW Cohort Study Group (FinELBW) (John Wiley and Sons, 2022)
Background and aims
Children with extremely low‐birth weight (ELBW) have a high risk for cognitive, motor, and attention impairments and learning disabilities. Longitudinal follow‐up studies to a later age are needed in order to increase understanding of the changes in neurodevelopmental trajectories in targeting timely intervention. The aims of this study were to investigate cognitive and motor outcomes, attention‐deficit hyperactivity (ADHD) behaviour, school performance, and overall outcomes in a national cohort of ELBW children at preadolescence, and minor neuromotor impairments in a subpopulation of these children and to compare the results with those of full‐term controls. The additional aim was to report the overall outcome in all ELBW infants born at 22 to 26 gestational weeks.
Methods
This longitudinal prospective national cohort study included all surviving ELBW (birth weight <1000 g) children born in Finland in 1996 to 1997. No children were excluded from the study. Perinatal, neonatal, and follow‐up data up to the age of 5 years of these children were registered in the national birth register. According to birth register, the study population included all infants born at the age under 27 gestational weeks. At 11 years of age general cognitive ability was tested with the Wechsler Intelligence Scale for Children, ADHD behavior evaluated with a report from each child's own teacher (ADHD Rating Scale IV), and school performance with a parental questionnaire. An ELBW subpopulation consisting of a cohort representative children from the two university hospitals from two regions (n = 63) and the age‐matched full‐term born controls born in Helsinki university hospital (n = 30) underwent Movement Assessment Battery for Children and Touwen neurological examination comprising developmental coordination disorder (DCD) and minor neurological dysfunction (MND), respectively.
Results
Of 206 ELBW survivors 122 (73% of eligible) children and 30 (100%) full‐term control children participated in assessments. ELBW children had lower full‐scale intellectual quotient than controls (t‐test, 90 vs 112, P < .001), elevated teacher‐ reported inattention scores (median = 4.0 vs 1.0, P = .021, r = .20) and needed more educational support (47% vs 17%, OR 4.5, 95% CI 1.6‐12.4, P = .02). In the subpopulation, the incidences of DCD were 30% in ELBW and 7% in control children (P = .012, OR 6.0 CI 1.3‐27.9), and complex MND 12.5% and 0%, (P = .052; RR 1.1 95% CI 1.04‐1.25), respectively. Of survivors born in 24 to 26 gestational weeks, 29% had normal outcome.
Conclusion
As the majority of the extremely preterm born children had some problems, long‐term follow‐up is warranted to identify those with special needs and to design individual multidisciplinary support programs.